Adam Smith: World Economic Forum 1995 Highlights
The television program contains highlights of the annual meeting of the World Economic Forum that took place in Davos, Switzerland between 26 and 31 of January, 1995 where George Soros was one of the panelists. The program features interviews with Boutros Boutros-Ghali, Herminio Blanco Mendoza, Dr. Maria Livanos Cattaui, Robert Hormats, Nursultan A. Nazarbayev, Boris Nemtsov, George Soros, Richard Perle, and Grigory A. Yavlinsky, as well as Adam Smith’s comments on the economic and political issues of the time.